THE PATCH-TEST MODEL OF LAYERED SOIL FOUNDATIONS OF FINITE ELEMENT METHOD - Petrenko, V. D.; Selykhova, T. O.; Tiutkin, O. L. (Science and Transport Progress, 2006)
The article presents practical recommendations on application of patch-test of finite element model of the stratified soil bases.